2016
DOI: 10.1097/gme.0000000000000644
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body vibration improves neuromuscular parameters and functional capacity in osteopenic postmenopausal women

Abstract: Low-intensity vibration improved balance, motility, and muscle strength in the upper and lower limbs in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…Whole-body MV has been clinically implemented as a therapy for a variety of musculoskeletal diseases, including osteoporosis 15 and OA 16 . A number of studies report beneficial effects of mechanical stimulation in bone 15,17,18 , muscle 19 and cartilage 16,20,21 . Vibration provides improvements in muscle strength 16,22 , pain reduction 16,23 and decreased plasma concentrations of inflammatory markers 23 in OA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Whole-body MV has been clinically implemented as a therapy for a variety of musculoskeletal diseases, including osteoporosis 15 and OA 16 . A number of studies report beneficial effects of mechanical stimulation in bone 15,17,18 , muscle 19 and cartilage 16,20,21 . Vibration provides improvements in muscle strength 16,22 , pain reduction 16,23 and decreased plasma concentrations of inflammatory markers 23 in OA patients.…”
Section: Introductionmentioning
confidence: 99%
“…At baseline, calf muscle CSA was significantly correlated with the BMD of the hip (R = 0.58, P = .0017) and spine (R = 0.55, P = .0034), suggesting that BMD at central sites in this population are better maintained in individuals with better musculature independent of any intervention. Paralleling these results, a recent study involving postmenopausal women undergoing whole-body vibrations with 60-Hz frequency and 0.6 g intensity showed significant improvement in muscle strength after 12 months of 20 min/d, 5 times per week intervention (48). It is likely that the changes we observed in bone were at least partly due to the effect of muscular stimulation on bone, in addition to direct stimulation of bone or mechanical coupling of osteocyte nuclei and the cytoskeleton as previously suggested.…”
Section: Discussionmentioning
confidence: 68%
“…Although not significant, the exercise when performed at the frequency of 35 Hz showed a greater HR variation in the COPD group. In this context, studies demonstrated that transmissions of vibrational stimuli to soft tissues seem to suffer an attenuation of the stimulus in the hip and spine joints at frequencies above 35 Hz (11). Pleguezuelos et al (22) adopted a WBV protocol with frequency of 35 Hz and demonstrated that there was an increase of 15 beats during each session of WBV in people with severe COPD.…”
Section: Discussionmentioning
confidence: 99%